UPAYA PENINGKATAN EFEKTIVITAS KERJA KANTOR CAMAT SIBOLGA SAMBAS DITINJAU DARI PELAKSANAAN KEGIATAN DIKLAT (PENDIDIKAN DAN PELATIHAN) - Koto, Mhd. Shafwan; Rani Saragih, Laila Gusti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the implementation (DIKLAT) of Education and Training in improving work effectiveness in the Sibolga Sambas Sub-District Office by appealing the hioptesis that there is an influence (DIKLAT) of Education and Training on the work effectiveness of the Sibolga Sambas Sub-District Office. The research method used is descriptive causal comperative method . The author uses 21 respondents as a sample drawn from the entire population. The results showed a positive relationship between (DILLAT) Education and Training with work Effectiveness at the Sibolga Sambas Sub-District Office of 0.953, so that when interpreted on a scale the values ​​could be categorized rather low. Regression equation obtained Y = 3.673 + 0.883 X which shows the effect of Education and Training on work effectiveness. The t test showed that the hypothesis was accepted to be correct, where t count 13.639> 2.09302, which means that work effectiveness would increase by a regression coefficient / slop (0.883) if the variable (DIKLAT) education and training were added by one unit. While the coefficient of determination is known that education and training only contribute 90.7% to the effectiveness of work in the Sibolga Sambas District Office and the remaining 9.3% is influenced by other factors not examined.